The Impact of Artificial Intelligence on Audit Efficiency - Shi Enze (SHS Web of Conferences)
In the era of digital transformation, traditional audit lags in handling data. Artificial Intelligence (AI) with its tech edge, has entered audit but its efficiency impact needs study. This qualitative lit review analyzes AI-used tech for audit efficiency, evaluation, improvement, risks and countermeasures. AI shortens audit cycle, cuts costs, and boosts accuracy. However, it has high development costs, lacks rational judgment, demands skilled staff, and risks data security. Strengthening industry-academia-research cooperation, man-machine collaboration, training, and data security can ease these issues. AI offers audit transformation, and addressing challenges will drive audit industry’s intelligent growth. For regulatory agencies, it offers insights to optimize regulatory policies, ensuring AI in audit is properly supervised. For audit firms, it provides guidance to enhance audit services using AI, improving competitiveness. For enterprises, it helps them make better use of AI-based audit results for more informed business decisions.